Karakteristik Kimia Pempek Akibat Penambahan Konsentrasi Ekstrak Kulit Buah Naga Dan Metode Penyimpanan - Anak Agung Putu Sri Mahayani; Amelia Nirmalawaty (FMIPA : Universitas PGRI Adi Buana, 2021)
The part of dragon fruit that is used is only the flesh of the fruit for direct consumption or processing as other food products, while the peel is just thrown away. Based on several research results, red dragon fruit peel is a rich source of polyphenols and antioxidants. The antioxidant activity of the red dragon fruit peel is greater than the activity in the flesh, so the dragon fruit peel can be used as a natural herbal medicine by utilizing the antioxidants inside. The more dragon fruit peel extract is added, the pempek's shelf life is longer than without the addition of dragon fruit peel extract (control), the use of vacuum plastic can increase the shelf life of pempek. Keywords: dragon fruit peel extract, pempek, physical properties, chemical properties